PENGARUH BRAND IMAGE DAN PRODUCT QUALITY TERHADAP PURCHASE INTENTION DIMEDIASI PROMOSI PADA PRODUK KOSMETIK MAYBELLINE - Hartanti, Puri Gita; Budiarti, Anindhtya (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2023)
This research aimed to aimed to find out whether Brand Image and Product Quality affected the purchase intention which was mediated by promotion. Moreover, the population was all the customers of Maybelline cosmetic products in Sidoarjo. Furthermore, there were 100 people as respondents. Moreover, the data analysis used path analysis with PLS. The data analysis technique used an inner model, outer model, hypothesis test, and mediate effect test. The result concluded that Brand Image did not affect promotion. However, product quality affected promotion. Additionally, brand image affected purchase intention. Likewise, product quality had affected purchase intention. In contrast, promotion did not affect the purchase intention. In addition, promotion was not able to mediate the relationship between brand image and purchase intention. Similarly, promotion was not able to mediate the relationship between product quality and purchase intention